Hypofractionated Prostate Radiotherapy with or without Conventionally Fractionated Nodal Irradiation: Clinical Toxicity Observations and Retrospective Daily Dosimetry - Andrew M. McDonald; Justin M. Bishop; Rojymon Jacob; Michael C. Dobelbower; Robert Y. Kim; Eddy S. Yang; Heather Smith; Xingen Wu; John B. Fiveash (Prostate Cancer)
Purpose. To evaluate toxicity associated with the addition of elective nodal irradiation (ENI) to a hypofractionated regimen for the treatment of prostate cancer. Methods and Materials. Fifty-seven patients received pelvic image-guided IMRT to 50.4 Gy in 28 fractions with a hypofractionated simultaneous boost to the prostate to 70 Gy. Thirty-one patients received prostate-only treatment to 70 Gy in 28 fractions. Results. Median followup was 41.1 months. Early grade ≥2 urinary toxicity rates were 49% (28 of 57) for patients receiving ENI and 58% (18 of 31) for those not (P=0.61). Early grade ≥2 rectal toxicity rates were 40% (23 of 57) and 23% (7 of 31), respectively (P=0.09). The addition of ENI resulted in a 21% actuarial rate of late grade ≥2 rectal toxicity at 4 years, compared to 0% for patients treated to the prostate only (P=0.02). Retrospective daily dosimetry of patients experiencing late rectal toxicity revealed an average increase of 2.67% of the rectal volume receiving 70 Gy compared to the original plan. Conclusions. The addition of ENI resulted in an increased risk of late rectal toxicity. Grade ≥2 late rectal toxicity was associated with worse daily rectal dosimetry compared to the treatment plan.